Raynaud’s phenomenon in the rheumatologist’s practice - R.T. Alekperov (Современная ревматология, 2014)
Raynaud’s phenomenon (RP) is a common condition that predominantly occurs among women. The onset age in most cases is under 30 years. The phenomenon was first described by M. Raynaud over 150 years ago. Primary (Raynaud’s disease) and secondary RP were subsequently distinguished. Pathophysiology of RP has not been fully elucidated yet; RP seems to be a multifactor disease. A pronounced vasospasm in response to stimuli is believed to be caused by disruption in the central and local mechanisms of regulation of vascular tonus. Vascular endothe- lial, intravascular, and neuronal disorders are the key ones among these factors. Structural changes in vessels that can be observed by nailfold capillaroscopy play a significant role in pathophysiology of secondary RP. The key step in the diagnosis of RP is identifying its clinical variant, since secondary RP may be a sign or a premonitory symptom of certain autoimmune, hematologic, endocrine, neoplastic, and other disorders. Secondary RP is most frequently observed in patients with systemic rheumatoid diseases. Therapy of secondary RP provides no satisfactory out- comes, since there is no complete conception about the pathophysiological mechanisms of its development. Different groups of drugs are cur- rently used to treat RP, including calcium channels blockers, phosphodiesterase type 5 inhibitors, endothelin receptor antagonists, etc. This review focuses on pathogenesis, the algorithm of early and differential diagnosis of RP, and current approaches to therapy based on the analysis of the published and our own data.